STYK1/NOK Promotes Metastasis and Epithelial-Mesenchymal Transition in Non-small Cell Lung Cancer by Suppressing FoxO1 Signaling - Lai, Yuanyang; Lin, Fang; Wang, Xuejiao; Zhang, Jiao; Xia, Jinghua; Sun, Ying; Wen, Miaomiao; Li, Xiaofei; Zhang, Zhipei; Zhao, Jinbo (Frontiers in Cell and Developmental Biology, 2021)
Aims: Serine/threonine/tyrosine kinase 1 (STYK1) has been previously shown to have oncogenic properties, and emerging evidence suggests that STYK1 expression correlates with epithelial-mesenchymal transition (EMT). However, the mechanism of STYK1 involvement in oncogenesis remains unknown. The present study aimed to elucidate how STYK1 expression level relates to the metastasis, migration, invasion, and EMT in non-small cell lung cancer (NSCLC) and to determine the molecular mechanism of STYK1 effects. Methods: STYK1 expression level and its relationship with the prognosis of NSCLC were determined using the ONCOMINE database and clinical cases. NSCLC cell lines with the overexpression or knockdown of STYK1 were established to determine whether STYK1 promotes cell migration, invasion, and EMT in vitro and in vivo. In addition, a constitutively active FoxO1 mutant (FoxO1AAA) was used to examine the role of FoxO1 in the STYK1-mediated upregulation of metastasis and EMT in NSCLC. Results: STYK1 was upregulated in NSCLC tissues and cell lines, and its overexpression correlated with poor prognosis in patients with NSCLC after surgery. Enhanced expression of STYK1 potentiated the migration, invasion, and EMT in SW900 cells, thereby promoting metastasis, whereas knockdown of STYK1 inhibited these cellular phenomena in Calu-1 cells. Furthermore, STYK1 expression was positively related to the level of phosphorylated-FoxO1, whereas the constitutively active FoxO1 mutant protected against the positive effect of STYK1 overexpression on cell migration, invasion, and EMT. Conclusion: STYK1 was upregulated in NSCLC and correlated with poor clinical outcomes. In addition, STYK1 suppressed FoxO1 functions, thereby promoting metastasis and EMT in NSCLC.